IMPLEMENTASI KEBIJAKAN DANA DESA DALAM PEMBANGUNAN INFRASTRUKTUR FISIK DI DESA GIRIPURNO KECAMATAN NGADIREJO KABUPATEN TEMANGGUNG - Maria Sri Hariyati, Ana; Zarkasyi Rahman, Amni; Hanani, Retna (Journal of Public Policy and Management Review, 2024)
The village fund is part of the transfer to the regions aimed at supporting the funding of governance, development, community empowerment, and community in the village. The purpose of this study was to describe the implementation of village fund policies in the development of physical infrastructure in Giripurno Village and identify the factors that influence the implementation process. This study uses descriptive qualitative methods with data collection through observation, interviews, and documentation. The theory used is the equation of phenomena from various models of top-down policy implementation. The results showed that the implementation of the village fund policy in the development of physical infrastructure in Giripurno village has not fully run according to the provisions of the current legislation because the village fund distribution process is still based on previous regulations. The supporting factors for policy implementation are sufficient human resources and equipment, clear and consistent communication between organizations, good disposition of implementers, and supportive environmental conditions in the form of open-minded people, livelihoods that focus on the agricultural sector, improving education levels and high enthusiasm of the community. Meanwhile, the factors that hinder the implementation process are inadequate budget resources, lack of maximum communication between organizations, and policy environment conditions that include low quality of society, strong paternalistic culture, diverse patterns of community behavior, and differences in income levels.